Zero Mortality During Covid-19 Outbreak: A Review in 418 Workers at a Health University - Sudiro, Sudiro; Satino, Satino; Setyorini, Yuyun; Ardesa, Yopi Harwinandha; Darmawan, Rendi Editya (JKG (JURNAL KEPERAWATAN GLOBAL), 2023)
Background: Mortality due to Covid-19 outbreak in Indonesia are the second highest in Asia on period 2020-2021, but there is one of health university that zero mortality. Some of the factors that cause high mortality are only assumptions from researchers, need to be clarified scientifically. Aim of study is to analyze factors that causes zero mortality during covid-19 outbreak.  Methods: We performed a descriptive study using result of medical check up workers within the first 1 year of the pandemic. All workers consist of lecturers, administrative staff, drivers, and cleaning staff were included as much as 418 persons. Patients were assessed for their gender, age, body mass index, blood pressure, total cholesterol, and electrocardiography based on laboratory test and interview. We analyze data using descriptive based on characteristics respondents. Data collected in December 2021. The examination is carried out by a certified laboratory.  Results: The age of the workers is mostly young, the small incidence of hypertension, hypercholesterolemia, and heart health problems, have the potential to be a reason for zero mortality during the covid 19 outbreak in 418 workers. Hypertension, gender, obesity, hypercholesterolemia, and aritmia unrelated to mortality, but related to severity.  Age directly related to mortality.  Conclusion: A healthy body is an asset in dealing with a pandemic. Periodic checks on blood sugar, electrocardiography, cholesterol, body mass index, is needed in preparing for the next pandemic minimum once every 6 months.